Top management team nationality diversity and firm performance: A multilevel study - Nielsen, Bo Bernhard; Nielsen, Sabina (Strategic Management Journal, 2013)
Abstract This research reexamines the equivocal relationship between top management team (TMT) diversity and firm performance. Combining upper echelons theory with insights from institutional theory, we establish a new, timely dimension of TMT diversity—nationality diversity—and develop an integrated multilevel framework explaining how its performance implications vary across contextual settings. We find that nationality diversity is positively related to performance; and this effect is stronger in (a) longer tenured teams, (b) highly internationalized firms, and (c) munificent environments. More generally, our research demonstrates that the consequences of TMT diversity depend on the (1) specific attributes of diversity being considered and (2) firm and industry conditions under which strategic decisions take place. Copyright © 2012 John Wiley & Sons, Ltd.